An intelligent tool for converting prolog problems into prolog codes / Wang Keng Kuen - Wang, Keng Kuen (2003)
A thesis presented in partial fulfillment of the requirements for the bachelor of computer science degree. This document is submitted Dr. Rukaini Haji Abdullah (thesis supervisor) and Ms Norisma ldris (thesis moderator), lecturers of FSKTM as a report for the final year project level one, WXES3181. intelligent prolog pseudocode converter (IPPC) are designed to allow novice programmer have an easier tool for them to get Prolog codes converted from the Pseudocode they had wrote. IPPC included documents to help guide users and teaching them about how to write program with using IPPC. The first part of the thesis presents about problems definitions for using Prolog in writing program and introduction of IPPC. The second part introduces the theoretical basis of the research and the methodologies employed to apply them. The final part described about the IPPC's requirement analysis and IPPC's design. For the next advancement stage, WXES3182, the final year project level One, WXES3181 is important as references in the actual coding and development in WXES3182. However, there may have be some changes to the system design in this proposal for WXES3182. The changes have been reflecting in the product and in this report.